sCD28, sCD80, sCTLA-4, and sBTLA Are Promising Markers in Diagnostic and Therapeutic Approaches for Aseptic Loosening and Periprosthetic Joint Infection - Jubel, Jil M.; Randau, Thomas M.; Becker-Gotot, Janine; Scheidt, Sebastian; Wimmer, Matthias D.; Kohlhof, Hendrik; Burger, Christof; Wirtz, Dieter C.; Schildberg, Frank A. (Frontiers in Immunology, 2021)
Aseptic prosthetic loosening and periprosthetic joint infections (PJI) are among the most frequent complications after total knee/hip joint arthroplasty (TJA). Current research efforts focus on understanding the involvement of the immune system in these frequent complications. Different immune cell types have already been implicated in aseptic prosthetic loosening and PJI. The aim of this study was to systematically analyze aspirates from knee and hip joints, evaluating the qualitative and quantitative composition of soluble immunoregulatory markers, with a focus on co-inhibitory and co-stimulatory markers. It has been shown that these molecules play important roles in immune regulation in cancer and chronic infectious diseases, but they have not been investigated in the context of joint replacement. For this purpose, aspirates from control joints (i.e., native joints without implanted prostheses), joints with TJA (no signs of infection or aseptic loosening), joints with aseptic implant failure (AIF; i.e., aseptic loosening), and joints with PJI were collected. Fourteen soluble immunoregulatory markers were assessed using bead-based multiplex assays. In this study, it could be shown that the concentrations of the analyzed immunoregulatory molecules vary between control, TJA, AIF, and PJI joints. Comparing TJA patients to CO patients, sCD80 was significantly elevated. The marker sBTLA was significantly elevated in AIF joints compared to TJA joints. In addition, a significant difference for eight markers could be shown when comparing the AIF and CO groups (sCD27, sCTLA-4, sCD137, sCD80, sCD28, sTIM-3, sPD-1, sBTLA). A significant difference was also reached for nine soluble markers when the PJI and CO groups were compared (sLAG-3, sCTLA-4, sCD27, sCD80, sCD28, sTIM-3, sPD-1, IDO, sBTLA). In summary, the analyzed immunoregulatory markers could be useful for diagnostic purposes as well as to develop new therapeutic approaches for AIF and PJI.